2018
DOI: 10.21577/0103-5053.20180182
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Potential of Natural and Semi-Synthetic ent-Kaurane and ent-Pimarane Diterpenes against Clinically Isolated Gram-Positive Multidrug-Resistant Bacteria

Abstract: In this work, a search for antimicrobial agents against multi-drug resistant (MDR) bacteria was undertaken. It involved two natural diterpenes of different basic skeletons, named ent-kaurenoic acid and ent-pimaradienoic acid, that were used as precursors to access 28 semi-synthetic derivatives that were also submitted to biological assays. All 30 substances were assayed against a set of seven clinically isolated MDR bacteria, including three Staphylococcus aureus strains. Results classified both natural compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Further investigations by Smith et al supported this hypothesis highlighting a possible complex formation between diterpenes and reserpine responsible for a reduction in activity [115]. Recently, Soares A.C. and co-workers analyzed the antibacterial activity of two natural diterpenes against a set of seven clinically isolated MRD bacteria, including three S. aureus strains [116]. The two diterpenes, the tetracyclic ent-kaurenoic acid and the tricyclic ent-pimaradienoic acid (Table 3, compound 32 and 33), featuring a different basic skeleton, were isolated from Mikania glomerata and Viguiera arenaria, respectively, and selected for this study according to the Urzúa hypothesis.…”
Section: Diterpenesmentioning
confidence: 94%
See 1 more Smart Citation
“…Further investigations by Smith et al supported this hypothesis highlighting a possible complex formation between diterpenes and reserpine responsible for a reduction in activity [115]. Recently, Soares A.C. and co-workers analyzed the antibacterial activity of two natural diterpenes against a set of seven clinically isolated MRD bacteria, including three S. aureus strains [116]. The two diterpenes, the tetracyclic ent-kaurenoic acid and the tricyclic ent-pimaradienoic acid (Table 3, compound 32 and 33), featuring a different basic skeleton, were isolated from Mikania glomerata and Viguiera arenaria, respectively, and selected for this study according to the Urzúa hypothesis.…”
Section: Diterpenesmentioning
confidence: 94%
“…In order to perform structure-activity relationships studies the authors developed several semi-synthetic derivatives from both natural diterpenes. The hydrogenated product derivative of 33 (Table 3, compound 34), resulted to be even more efficient as an antimicrobial agent against MRSA and S. capitis with a MIC of 6.25 µg/mL [116]. Furthermore, Barbosa et al reported the potent antibacterial activity of the ent-kaurenoic acid isolated from C. reticulata oleoresin against MRSA (IC 50 3.4 µg/mL) [117].…”
Section: Diterpenesmentioning
confidence: 99%
“…Muitos trabalhos na área de produtos naturais vêm buscando obter moléculas isoladas de plantas devido atividade tóxica a cepas de bactérias patógenas resistentes (VAIČIULYTĖ, et al, 2021). As substâncias de origem natural têm sido fonte de moléculas ativas ou precursoras de outras moléculas semissintéticas no combate às doenças relacionadas a bactérias patógenas, em substituição a moléculas totalmente sintéticas (SOARES et al, 2019;NEWMAN & CRAGG, 2020).…”
Section: Introductionunclassified